La dactiloscopia: un arma contundente contra el delito de fleteo (2016)
The present study was performed to examine a crime in the form of freight costs in the light of criminology theory and its methodological proposal. Thus, the case study was organized according to the structure of the scientific method applied to the crime investigation, to know: problem statement, observation, hypothesis, methodology, data collection, theory and conclusions. During the analysis of what happened, however, fingerprinting and type of crime were the two most important aspects acquired and consequently that more attention was paid to them. An emphasis confirming the importance of understanding and characterization of the crimes, and especially the Embryology and Morphology of Friction Ridge Skin as a fundamental tool for identifying both the clarification of the facts and prosecuting those responsible, and to the deterrence, given its effectiveness, of many events of a criminal nature